2020
DOI: 10.1007/s11695-019-04352-y
|View full text |Cite
|
Sign up to set email alerts
|

Single Anastomosis Duodenal Switch: 1-Year Outcomes

Abstract: Introduction Single-anastomosis duodenal switch has been suggested to be an effective bariatric procedure that offers excellent weight loss and by lengthening the common channel the potential to reduce micronutrient deficiencies. Purpose To evaluate the weight loss, comorbidity resolution and the 1-year nutritional outcomes of the single-anastomosis duodenal switch (SADS) procedure. Setting Multiple US Hospitals. Methods From October 2014 to January 2017, 120 patients were enrolled at six sites across the USA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 27 publications
(33 reference statements)
1
3
0
2
Order By: Relevance
“…24 Cottam et al showed that there was a significant reduction of BMI from baseline 46.8 ± 5.8 to 29.8 ± 4.4 kg/m 2 at 1 year follow-up after LDS surgeries. 25 Weight-loss response in our patients was similar to the results shown in these studies. Studies have shown similar %TWL after LDS surgeries and BPD-DS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…24 Cottam et al showed that there was a significant reduction of BMI from baseline 46.8 ± 5.8 to 29.8 ± 4.4 kg/m 2 at 1 year follow-up after LDS surgeries. 25 Weight-loss response in our patients was similar to the results shown in these studies. Studies have shown similar %TWL after LDS surgeries and BPD-DS.…”
Section: Discussionsupporting
confidence: 91%
“…Cottam et al showed diabetes remission of 96.3% at a 1 year follow-up after the single anastomosis duodenal switch (SADS). 25 Independent samples t test c Significance when the common channel length was taken as an independent variable similar in the common channel subgroups in our study indicating that the common channel length can be increased from 2.5 to ≥3 m in LDS surgeries, without altering metabolic efficacy. The anastomosis is placed distally in the ileum in LDS surgeries, and this probably correlates with a potent ileal brake mediated by an enhanced secretion of Peptide YY and GLP1 which stimulate early satiety.…”
Section: Discussionmentioning
confidence: 71%
“…The Verhoeff et al meta-analysis weighted mean remission rate for T2D of 87.4% following SADI-S (measured at longest follow-up, 28.8 months) [ 27 ] was similar to that of the current study at 1-year follow-up notwithstanding its small sample size. In a prospective multicenter study of primary SADI-S by Cottam et al (2020) at 1-year follow-up, in SADI-S patients, T2D in 54/57 of patients (96.0%) was either resolved or improved with continued medications [ 29 ]. In relation to recent studies of SADI-S (and SADI-S vs DS), side-to-side MS DI + SG appeared to achieve a comparable rate of T2D resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Among the previous series, Sanchez-Pernaute et al [ 19 ] demonstrated the efficacy of SADI in a population of 97 diabetic patients, achieving control of the disease in 70–84% of patients long-term, and %EWL of 98 at 5-year follow-up. SADI was effective also in improving the patients’ quality of life [ 20 ]. A large series by Finno et al [ 21 ] compared 259 patients undergoing DS with 181 who had SADI-S (single-anastomosis duodeno-ileal bypass with sleeve gastrectomy).…”
Section: Discussionmentioning
confidence: 99%